Supramolecular luminescent system based on 2-cyano-3(4-(diphenylamino)phenyl) acrylic acid: Chiral luminescent host for selective CH3CN sensor - Draper, Sylvia; Delaney, Colm (My University, 2011)
New supramolecular luminescent host systems based on 2-cyano-3(4-(diphenylamino)phenyl) acrylic acid (CDPA), a triphenylamine based luminescent acid, and amines (propylamine (1), dimethylaminopyridine, DMAP (2) and (1S,2R)-2-amino-1,2-diphenylethanol (3)) were prepared using a supramolecular approach. For each, the inclusion of amines in the CDPA matrix led to blue shifts in the solid state luminescence. 1 forms a CH3CN-selective, luminescent host and exhibits solvent dependent luminescent changes in the solid state. Crystallisation of CDPA-DMAP from EtOAc (2a) and CH3CN (2b) produces two different solid forms which exhibit slight differences in luminescence (?max at 522 nm and 529 nm, respectively). The chiral luminescent host system (3a) obtained from CH3CN shows robust, reversible CH3CN-selective luminescent sensing (?max at 523 nm (with CH3CN) and 553 nm (without CH3CN)). In this case the luminescence changes with the crystallising solvent (MeOH (3b) and EtOH (3c)).
PUBLISHED
Keywords: Chemistry; Nanoscience & Materials; Smart & Sustainable Planet